Box-Behnken Experimental Design for Electrochemical Aptasensor Optimization on Screen Printed Carbon Electrode/Silica-Ceria - Zakiyyah, Salma Nur; Eddy, Diana Rakhmawaty; Firdaus, Muhammad Lutfi; Subroto, Toto; Hartati, Yeni Wahyuni (Syarif Hidayatullah State Islamic University, 2023)
This study aims to optimize the epithelial sodium channel (ENaC) electrochemical aptasensor with the Box-Behnken experimental design. ENaC is a protein that plays a role in sodium ion transport in several epithelial tissues and is associated with hypertension. The ENaC protein aptamer is held in place in the electrochemical aptasensor by a modified screen-printed carbon electrode (SPCE) of silica-ceria composite (SiO2-CeO2). The unique structure of a silica matrix with high biocompatibility can form composites through a hydrothermal process. The Box-Behnken (BBD) experimental design is an efficient optimization method of factors that affect the experiment at three levels. The FTIR results of the silica-ceria composites were 549.35 cm-1 (Ce-O), 1095.3 cm-1 (Si-O-Si), and 491.28 cm-1 (Si-O). Meanwhile, SPCE/silica-ceria characterized by differential pulse voltammetry (DPV) showed an increase in peak current [Fe(CN)6]3-/4- from 3.190 μA to 9.073 μA. Three experimental factors, aptamer concentration, streptavidin incubation time, and aptamer incubation time, were optimized with BBD and obtained at 0.5 μg.mL-1, 30 minutes, and 1 hour. The optimum conditions observed resulted in a selective current response for ENaC protein detection. The optimization results can be applied to aptamer-based ENaC protein detection in samples.